Microbial decomposition of Longan leaf: II. screening of effective cellulolytic microorganisms and development of microbial product prototype for accelerating composting process - Shutsrirung, Arawan; Kudreaung, Pattarin; Chromkaew, Yupa; Chinachanta, Kawiporn; Chaiwan, Fapailin (Asia-Pacific Journal of Science and Technology, 2020)
Microorganisms are the main decomposer of cellulose, hemicellulose and lignin in composting process. In the present study, we screened bacteria, fungi and actinomycetes showing high cellulolytic activity from longan leaves + cow dung (LC). The results showed that Comf3004 gave the highest clear zone ratio (3.5). Three isolates exhibited the highest Carboxymethyl (CM) case activity were bacterial isolate Comb3012 (0.596 U/mL), fungal isolate Comf6012 (0.875 U/mL) and actinomycetal isolate Comac9009 (0.525 U/mL). The LC was inoculated with the prototype of three selected microbial inoculants; LC+Comb3012 (LCb), LC+Comf6012 (LCf), LC+Comac9009 (LCac) and the mixture of the three inocula (LCbfac). The LC plus sterile carrier (LCC) was also applied for comparison. Over 120 days, the maximum germination index (GI) value (95.13%) was recorded in LCf. The LCf and LCb compost exhibited a remarkably low organic matter (OM) content (23.0 and 26.3%, respectively). The results indicated that inoculation of microbial inoculants could effectively accelerate the decomposition of LC. The nutrient contents of all treatments with microbial inoculation were also higher than LC and LCC. The lowest cellulose and hemicellulose content were obtained with LCf (18.5 and 12.5%, respectively). Moreover, the lowest content of lignin was obtained with LCac (4.9%). All inoculated treatments exhibited higher degradation of cellulose, hemicellulose and lignin than the control and sterile carrier treatments. Fungal isolate Comf6012 performed the best in breaking down cellulose and hemicellulose fractions while actinomycetal isolate Comac9009 exhibited the highest lignin degradation. The results highlight the high possibility in the application of effective microbial inoculum for rapid composting process of longan leaves.